Risk Factors for Cardiac Complications in Patients With Pheochromocytoma and Paraganglioma: A Retrospective Single-Center Study - Zhao, Lin; Meng, Xu; Mei, QiMin; Fan, Hua; Liu, YeCheng; Zhou, XianLiang; Zhu, HuaDong; Zhang, ShuYang (Frontiers in Endocrinology, 2022)
Background Catecholamine excess arising from pheochromocytomas and paragangliomas (PPGLs) can cause a wide spectrum of cardiac manifestations. Although there are reviews of reported cases, these reviews lack detailed data, which makes it impossible to perform an accurate analysis. In this study, we conducted a comprehensive analysis of cardiovascular complications (CCs), including PPGL-related myocardial injury, cardiogenic shock, and arrhythmias requiring antiarrhythmic therapy, in a large cohort of patients with PPGL. Methods We retrospectively analyzed the clinical data of consecutive patients with PPGL admitted between January 2018 and June 2020. The prevalence and the characteristics of patients with CCs were investigated. Moreover, comparisons were made between patients with and without CCs. Results Compared with the non-CC group, the percentage of men was significantly lower (14/41 vs.92/175, 34.1% vs. 52.6%, p = 0.034) and the proportion of patients with paroxysmal hypertension was significantly higher (13/41 vs.29/173, 31.7% vs.16.8%, p = 0.03) in the CC group. More patients showed excessive sweating (19/41 vs 64/175, 46.3% vs. 24.0%, p = 0.004) and PPGL crisis (7/41 vs. 10/175, 17.1% vs.5.7%, p=0.035) in the CC group. In terms of laboratory findings, higher white blood cell [7.36 (6.49, 20.23) vs. 5.95 (5.1, 6.97)×109/L, p<0.001] and platelet [339.28 ± 108.54 vs. 250.66 ± 70.83(×109/L), p = 0.021] counts were more common in the CC group. There was also a higher prevalence of combination-producing PPGL in the CC group (13/24 vs.20/149, 54.2% vs.13.4%, p<0.001). However, the tumor size, invasive behavior on histology, and hemorrhage or necrosis on histology did not differ between the two groups. Platelet count [odds ratio (OR): 1.009; 95% confidence interval (CI) 1.001–1.016; p=0.023] and combination-secreting PPGL (OR: 5.009; 95% CI 1.365–18.38; p=0.015) are independent risk factors for CCs in patients with PPGL. Conclusions In patients with PPGL, even in the absence of signs and symptoms of CCs, a work up of cardiology should be strongly considered. Importantly, if patients with PPGLs have higher platelet counts and the combination-secreting pattern, they are more likely to have CCs. Thus, a careful cardiac evaluation should be performed.